Enhancing the five-tier diagnostic test on cell concepts through Rasch model analysis - Silaban, Oky Rizkiana; Kusnadi, Kusnadi; Wulan, Ana Ratna (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2025)
Misconceptions in biology can prevent students from gaining a deeper understanding of biological concepts. There is a five-tier diagnostic test that can explore the misconceptions experienced by students. This research aims to develop a five-tier diagnostic test that is feasible to use to identify student misconceptions with Rasch model analysis. The research method used was quantitative descriptive, and the sample was 103 people with a purposive sampling technique, which is a purposeful sampling technique, namely, the school that is the research location, experiencing misconceptions related to the concept of cells. Based on the results of the study, it was found that the five-tier diagnostic test developed was very feasible to use as an instrument to identify students' misconceptions on the concept of cells. Each indicator is represented by several items that have been tested for validity, reliability, difficulty level and differentiation using Rasch model analysis with the help of the Winsteps program. Based on the analysis with the Rasch model, out of 36 items that were externally validated, 23 items were obtained that met the eligibility criteria and were declared valid for implementation.